The Impact of Economic Openness on Economic Growth in Aceh Province - Nur Maghfirah; Tony Irawan; Lukytawati Anggraeni (Signifikan: Jurnal Ilmu Ekonomi, 2022)
Economic openness is part of the demands that impact the entire region on economic development. This research aimed to analyze the impact of Economic Openness on Economic Growth in Aceh Province. The data used in this research was time-series data from 2005-2019. The variables used were exports, imports, domestic credit such as investment credit, consumer credit, working capital credit, and foreign investment (FDI). The data analysis tool used was a dynamic model with a specific approach to Autoregressive Distributed Lag (ARDL) model. The results of this research showed that in the long term, export, import, consumer credit, and working capital credit significantly affected Aceh’s economic growth. Then, the estimation results in the short term showed that import and consumption credit directly affect economic growth. Likewise, the result of Foreign Direct Investment (FDI) in the short term had a significant impact on Aceh’s economic growth. The government must strive to improve Economic openness because the impact is interrelated to national income and affect Aceh’s economic growth.How to Cite:Magfirah, N., Irawan, T., & Anggraeni, L. (2022). The Impact of Economic Openness on Economic Growth in Aceh Province. Signifikan: Jurnal Ilmu Ekonomi, 11 (2), 239-252. https://doi.org/10.15408/sjie.v11i2.21091.